2009
DOI: 10.1080/01421590802203488
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey for challenging cases of medical professionalism in Japan

Abstract: Many Japanese physicians were unable to provide an acceptable response to challenges to professionalism in several issues and few had received education in professionalism during school curricula. Greater teaching of professionalism is needed in medical education in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 15 publications
1
19
2
Order By: Relevance
“…It has been reported that Japanese doctors commonly encounter challenges in demonstrating medical professionalism 12 . At the same time, public attention to medical professionalism has recently increased in Japan 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Japanese doctors commonly encounter challenges in demonstrating medical professionalism 12 . At the same time, public attention to medical professionalism has recently increased in Japan 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessing professionalism among clinical trainees is of great importance and interest in Japan. However, few studies have reported on the development and implementation of professionalism assessment tools, except for a recent study using a Japanese version of the Barry Questionnaire 12 . Thus, tools for multi‐perspective professionalism assessment currently available in Japanese are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The Barry Professionalism scores focus on six limited areas of professionalism, but professionalism includes more than just these attributes. The Barry Professionalism questionnaire has been internally and externally validated (Barry, 2000;Tokuda, 2009) [8,12], but a more thorough evaluation could be performed with more extensive testing, to evaluate the impact of this curriculum on other aspects of professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…"Best" answers on the multiple choice Barry are given a score of two, acceptable answers are given a score of 1, and other answers are given a score of 0. The Barry was selected to assess resident professionalism because it was a short, externally validated, convenient questionnaire (Barry, 2000;Tokuda, 2009) [8,12].…”
Section: Methodsmentioning
confidence: 99%
“…Examples of such breaches in the medical education environment are: attempts to use personal relationships, bribes, or threats to gain academic advantage; cheating in a written exam; plagiarizing an entire essay assignment; forging a faculty signature on a patient chart; providing false information to delay writing an exam; and sabotaging another student's work (Teplitsky et al 2002). However, the literature indicates that research based on hypothetical scenarios have been found too complex to achieve a consistency of appropriate responses from a professional team (Tokuda et al, 2009). In this regard Roff and her colleagues (2011;2011a;2012) conducted studies to identify behaviors and attitudes that exhibit poor professionalism and determine a set of agreed levels of sanctions for unprofessional behaviors relating to academic integrity at various levels of medical education.…”
Section: Introductionmentioning
confidence: 99%